BRAVERY IN RICK RIORDAN’S THE BLOOD OF OLYMPUS (A CHARACTER ANALYSIS) - Thalia Takaliuang; Ceysi Nihta Wuntu; Delly Sabudu (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2022)
This research intends to depict Bravery in Rick Riordan’s The Blood of Olympus. This research is classified as qualitative research because the data are in the form of words rather than numbers. The objective approach is used to analyze Rick Riordan’s The Blood of Olympus. It means that Riordan’s work is analyzed in isolation from all these external points of reference, analysis as a self-sufficient entity constituted because this approach has a relationship with the novel. The finding shows that bravery depicted in the novel can be seen through the Discretion of a Piper McLean. There also existed the power against bravery and Reyna’s mission in combat. The novel is one of the literary creations that have real quality. Besides that, reading a novel is influential for the reader’s life, because we can understand as well as realize the real condition and life of the story in the novel.